Masses, Leaders and Crisis. A Comparison between Four Theoretical Frameworks - Somaini, Pietro (Philosophical journal of conflict and violence, 2019)
In the 20th century the occurrence of revolutions, violent collective behaviours and dictatorships have shown the power of masses, raising many theoretical issues in sociology, philosophy and psychology. In this paper, we will focus on four accounts in order to clarify the relation between a mass of human individuals and the role of a leader. These explanations are developed respectively by Weber, Le Bon, Freud and Girard. Even if our work is theoretical, we will briefly mention theFrench Revolution as solid example for a better understanding of mass-leader relation.